Unknown monumentum from the library of Sigismund II August in the collection of the Archdiocesan Archives in Gniezno - Muraszko, Michał (Folia Toruniensia, 2018)
Aim: The presented volume constitutes the monumentum of King Sigismund II August, hitherto unknown to the literature on the subject. It was discovered during works carried out under the grant project: “Inventory of the library of the cathedral library in Gniezno”. Research method: A formal analysis of the volume supplemented by a review of the literature of the subject matter. Conclusions: The book contains the work Germaniae exegeseos written by Franciszek Irenicus, which appeared in 1518 in Hagenau in the publishing house of Thomas Anshel, being issued by Johann Koberger. The book binding, bearing the monarch’s bookmarks, was created in 1560 in the second bookbindery in Vilnius. The volume is deprived of old signatures, notes and property marks that could indicate how it had become part of the collection of the Archdiocesan Archives in Gniezno.